19th CENTURY WOMEN AND HOMOSEXUALITY: THE CASE OF VIRGINIA WOOLF'S MRS. DALWWAY - Angelika Riyandari (Soegijapranata Catholic University, 2001)
Woolf's Mrs Dalloway portrays the experience of a 19th century woman in dealing with homosexuality. The incapability to show affection to the same sex, the denial of the feeling and the strunggle to keep the love leads the woman to an emotional suicide. The woman's choice to marry a man, have a child, and play her role as a sophisticated housewife are the ways to compromise with the norms and conventions if that age where home was the centre of woman's life